Synthesis of Cu3.21Bi4.79S9 bismuth chalcogenide by mechanical alloying - Barma, M.C.; Long, B.D.; Sabri, Mohd Faizul Mohd; Ramesh, Singh; Saidur, R.; Said, Suhana Mohd; Kimura, K.; Hai, N.H.; Huy, T.D.; Trung, T.B. (Elsevier, 2016)
In this research, Cu3.21Bi4.79S9 was synthesized from Cu, Bi and S powders using ball milling. The effects of ball milling duration and the process control agent, i.e. ethanol, on the formation of Cu3.21Bi4.79S9 were investigated. The thermal stability of Cu3.21Bi4.79S9 was also studied using a Differential Scanning Calorimeter (DSC) in combination with X-ray diffraction (XRD) analysis. It was observed that the addition of ethanol shows a significant effect on the refinement of the particle size of the milled powder. However, ethanol showed a negative effect on the formation of single phase Cu3.21Bi4.79S9 during ball milling. Cu3.21Bi4.79S9 was found in the milled powder after milling for 5 h without using ethanol, whilst the presence of secondary phases such as Bi2S3 and Cu2S were also detected. All these secondary phases were disappeared after milling for 15 h. Prolonged milling duration did not produce any change in the phases. Minimum particle size of the milled powder was achieved around 0.251 μm after milling for 25 h. The XRD and DSC results showed that Cu3.21Bi4.79S9 is thermally stable up to 230 °C.